'Organising objects': support for legal capacity in adult safeguarding and Article 12 of the UN Convention on the Rights of Persons with Disabilities - Keeling, Amanda (2017)
This thesis explores social workers’ practice and understanding of support for the exercise of legal capacity in adult safeguarding. The impetus for this study was the ‘revolution’ of article 12 of the UN Convention on the Rights of Persons with Disabilities, which questioned fundamental and long-held legal positions on the rights of people with mental impairments to make decisions about their lives. This shift is a fundamental one, but there is very little existing empirical evidence of how such a revolutionary change in legal frameworks might actually work in practice, and what the challenges may be. Thus, this thesis aimed to empirically examine existing practice, to explore what the baseline of understanding was, and the difficulties that social workers encountered in using support mechanisms. An ethnographic approach was taken, with participant observation of an adult safeguarding team over a 17 week period, followed by interviews with 7 of the social workers who had been closely observed.